Conditions in Maternity Wards and Childbirth Experiences in Serbia, Bosnia and Herzegovina, Montenegro, and Croatia - Šunjka Ćorković, Jasmina; Đurica, Marko; Marić, Tiana Alexandra; Kamenović, Hristina (24th Psychology Days in Zadar: Book of Selected Proceedings, 2026)
Various factors, including individual, interpersonal, and unexpected medical issues, play significant roles in shaping women’s childbirth experiences. In response to the scarcity of research in this domain across the Balkan countries, this study offers foundational insights into the conditions prevalent in maternity wards and the intricacies of childbirth experiences. To achieve this, we constructed an online questionnaire which was completed by a total of 10,657 respondents from Serbia, Montenegro, Bosnia and Herzegovina, and Croatia, who gave birth between 2000 and 2021. In order to minimise the influence of potential confounding variables resulting from changes in obstetric care practices over the past two decades, data analysis was limited to the participants who gave birth between 2016 and 2021 (N= 7,779). Data were analysed using descriptive statistics, as well as content analysis for an open-ended question regarding adverse experiences during childbirth and hospitalisation. The most significant findings of this study highlight widespread issues of bribery and corruption within maternity wards, with nearly 50% of the respondents across all four countries reporting the use of personal connections with hospital staff to secure adequate care. Psychological support post-childbirth was alarmingly insufficient, with fewer than 5% of women receiving any form of assistance, despite 28.5% to 35.0% of the participants reporting symptoms of postpartum depression. Particularly noteworthy outcomes of the content analysis were instances within the staff category, where the respondents reported various forms of mistreatment and substandard care. These results underscore the necessity for further dedicated research on this pivotal topic.